(untitled) (Andamios, Revista de Investigación Social, 2011)
The goal of this text is to develop an internal defense of the social rights’ inclusion in the essential rights’ catalog. It´s called internal defense because it is necessary the inclusion of such rights for the realization of the sense of justice. Unlike the positivist’ tradition, which considered that it was possible to describe the judicial legislation as neutral; what this article approaches is that the law, as a social artifice, must be understood in order to make an adequate descriptive work. As long as the dynamics of the law suppose all the participants’ freedom (the actions could be imputed to them) its sense is constituted by the conditions that allow such freedom. This strategy to defend the social rights was the principal contribution of the socialist´ tradition. However, the efficacy of the social rights depends on their indissoluble link with the civil and political rights.